Towards Inclusive Learning: Evaluation of Disability Accommodation Policies for Educational Equity - Esa Septian; Septi Wulandari (Universitas Sebelas Maret, 2025)
This research aims to evaluate government policy in the form of Government Regulation Number 13 of 2020 concerning Appropriate Accommodation for Learners with Disabilities and the changes brought about by the policy. To support education for children with disabilities in getting an education by guaranteeing accommodation in disability limitations there are physical, intellectual, mental, and sensory. This consists of budget or funding assistance, facilities and infrastructure, educators and education personnel, and an education curriculum that supports the learning process of children with disabilities. This research method uses systemic literature review and meta-analysis in policy evaluation by determining strategies and criteria for systematic literature review searches. The results of the literature review are then analyzed using formal evaluation to produce reliable and valid information about policy outcomes that have been officially announced as policy program objectives. The results of this study show promising early results in inclusive education, where students with disabilities can participate in learning activities well. People with disabilities have an equally strong passion for learning independence and social equity for all. Coordination between institutions, stakeholders, and parties related to learners with disabilities needs to be formulated to support social engagement. The policy has an impact on Objective mapping, Value clarification and Critique, Cross-impact analysis, and Discounting.